The relations between marital quality, social support, social acceptance and coping strategies among the infertile Iranian couples. (May 2016) - Yazdani, Fatemeh; Kazemi, Ashraf; Fooladi, Marjaneh M.; Samani, Hamid R. Oreyzi
Abstract: Objective: Researchers aimed to assess marital quality among the infertile couples undergoing assistive reproductive treatments and their coping strategies, social support and social acceptance. Methods: In a cross-sectional study, 133 infertile couples undergoing assisted reproductive treatments were assessed for marital satisfaction, conflict resolution and marital communication, and coping strategies, using a self-report questionnaire. Also, the level of perceived social support and social acceptance as moderator variables were measured. Data were analyzed using independent t test, Pearson correlation coefficient, and linear regressions, after adjusting for age, cause of infertility and the duration of infertility. Results: No significant difference was found in the use of various coping strategies between couples. The correlation for marital satisfaction, marital communication and conflict resolution by using some coping strategy and the level of perceived social acceptance were significantly positive among women. Also, marital relationships had a positive and significant correlation with the level of perceived social support for men. But, unlike women, the couples' scales were significant for the perceived social support. The use of different coping strategies by men and women had a positive correlation with their perceived social support. Conclusion: Coping strategies used by the infertile couples had an important role in different aspects of their married life in search of marital satisfaction, and intermediates by the perceived social acceptance for women and social support for men.